Histopathological evaluation of renal allograft biopsies: a single center study in Dhaka, Bangladesh (BIRDEM Medical Journal, 2025)
Background: Renal transplantation is gradually increasing in Bangladesh due to introduction of live transplantation procedure in some of the urology centers in Dhaka. Graft dysfunction followed by graft failure is one of the worst complications of renal transplantation and graft biopsy is the gold standard to evaluate the cause of failure in addition to clinical parameters. This study was designed to evaluate the causes of graft dysfunction according to Banff classification and correlation with clinical and laboratory parameters. Methods: All the renal graft biopsy samples received at Armed Forces Institute of Pathology during the period from July 2020 to June 2022 were included in the study. Standard histological procedure for renal biopsy including special stains (PAS, Masson Trichrom, Silver) and DIF (IgG, IgA, IgM, C3, C1q, Kappa, Lambda) were applied for all the cases. Immunohistochemistry for C4d and CD3 were also performed for each case. Polyoma virus marker could not be evaluated due to unavailability. BANFF classification was done with the available findings. Results: Total 23 cases were included in this study. All the cases were from live related donors. Mean age of the patients was 34.39 years with male: female ratio 2.28. Time of kidney biopsy from renal transplantation varied from 7 days to 130 months with the average 27.66 months. Graft dysfunction was the indication of the biopsy with average serum creatinine 4.23 mg/dl (range 1.15 to 12.4 mg/dl). Ten (43.48%) of the patients had proteinuria ranging from 1.5 gm to 3 gm/24 hours and 7 (30.43%) patients had haematuria. Among all the cases, 10 (43.48%) came out as Banff category 2 (antibody mediated rejection, ABMR) among them 9 was acute ABMR and one was chronic ABMR. The next common Banff category was Banff 6 (6, 26.09%), which includes IgA nephropathy (2), MPGN (1), CNI toxicity (1), crystal nephropathy (1) and RCN (1). Three (13.04%) were diagnosed as Banff-4 (T cell mediated rejection, TCMR), one (4.34%) was Banff-3 (borderline) and one (4.34%) was Banff-5 (IFTA). Mixed category was observed in 2 cases (Banff-2 + Banff-6). None of the case was diagnosed as Banff-1. Mean age of ABMR was 34.92 years, average duration since transplantation was 20.93 months and mean serum creatinine level was 3.67 mg/dl. Mean age of patients having TCMR was 38.33 years, average duration from transplantation was 59.33 months and mean serum creatinine level 4.71 mg/dl. CNI toxicity was found in a female of 16 years after 10 days of transplantation. One 55 years diabetic male developed graft dysfunction due to crystal nephropathy. One 28-year-old male developed anuria after 7 days of transplantation and diagnosed as post transplant RCN. A 45-year-old male had graft dysfunction after 5 years of transplantation with very high serum creatinine level (12.4 mg/dl) diagnosed as IFTA. Conclusion: Acute ABMR was found to be the prime cause of graft rejection in this study which occured mostly within 2 years of renal transplantation. TCMR occured mostly after 3 years of transplantation. Graft dysfunction due to other than rejection covered 30.43% cases.BIRDEM Med J 2025; 15(1): 28-33